Coupling effect of impact and in-layer voltage on flexoelectricity of PDMS laminated structures. (November 2022) - Chang, Mengzhou; Li, Ke; Liu, Chang; Leng, Bingyu; Guo, Kai; Chen, Chuang; Han, Yafei; He, Liping; Tang, Enling
Abstract: The low flexoelectric coefficients of polymers are the key problem that limit their application. In this paper, electret-like PDMS/metal conductive layer/PDMS laminated structures have been prepared, an internal electric field are applied on the metal conductive layer aimed at improving electromechanical response. Experiments on the flexoelectric responses of polymer laminated structures under impact are performed based on SHPB, in-layer voltage supply system and polarization voltage measuring system. Numerical simulations are also conducted to investigate the dynamic stress-strain relationship and polarization characteristics of polymer laminated structure under different in-layer voltages. The results show that maximum stress increases with decreasing in-layer voltage; the maximum polarization voltage increases first and then decreases with absolute value of in-layer voltage; the minimum polarization voltage decreases with absolute value of in-layer voltage. Specimen with negative voltage has advantage of conversing electric energy and transferring charges. The impact induced strain gradients have been investigated based on numerical simulation and the related flexoelectricity coefficients are obtained. Addition of metal conductive layer and application of in-layer voltage are effective ways to enhance flexoelectricity. Highlights: Coupling effect of impact and in-layer voltage on PDMS/metal conductive layer/PDMS laminated structures is generally studied. Supplying in-layer negative voltage can induce additional electric field which contributes to the flexoelectricity. Rigid layer can increase the average strain gradient of PDMS under impact. Flexoelectric coefficients μ zzzz, μ rrrz and μ θθrz of PDMS structures are 4.83 × 10 −10, −5.86 × 10 −10 and 2.61 × 10 −9 C·m −1